Surface qualities have little effect on vection strength - Ogawa, Masaki; Hiramatsu, Chihiro; Seno, Takeharu (Frontiers in Psychology, 2014)
We investigated the effects of different surface qualities of materials on vection strength. Previous studies have extensively examined the stimulus parameters for effective vection induction. However, the effects of surface qualities on vection induction have not been studied at all despite their importance in realistic perception of a scene. As a first step toward understanding the effects of surface qualities on vection, we investigated surface qualities derived from light-reflecting properties of nine material categories commonly encountered in daily life: bark, ceramic, fabric, fur, glass, leather, metal, stone and wood. To relate vection strength with low-level visual features and with subjective impression of materials, we analyzed spatial frequency and participants' ratings of adjective pairs that describe impressions of material categories. Although the nine material categories were perceived differently, there was no main effect of material condition on vection strength. However, multiple regression analyses revealed that vection was partially explained by both spatial frequency and principal components extracted from the subjective impression. These results indicate that although the effect of surface qualities of materials on vection is small, both low-level image-based and perceptual-level processing of surface qualities may influence vection1.